Determinação de área de superfície específica em amostras de grafeno através do efeito de quenching da fluorescência - Douglas dos Santos RIbeiro (2024)
One of the main routes to produce graphene on a large scale is liquid phase exfoliation (LPE). The determination of the Specific Surface Area (SSA) is crucial for the characteri- zation of these materials. In a primitive cubic lattice with 1,000 atoms, 488 are on the surface; however, in a two-dimensional single-layer lattice, all atoms are on the surface, interacting chemically with the surrounding medium and defining the functionalities of the nanostructure. Thus, one of the most significant morphological properties at the nanometer scale is the specific surface area, which determines reactivity levels. An alternative method can be developed by optical spectroscopy to measure the Surface Area concentration (ρA) of graphene nanoflakes in liquid dispersions. The information is obtained by reducing the fluorescence signal of the dye molecules. The quantum efficiency of fluorescence decreases exponentially with the concentration of graphene surface area, regardless of the degree of exfoliation of the material. If the mass concentration (ρ) is known, the SSA can be calculated as ρA/ρ. These measurements are helpful for quality control of two-dimensional nanomaterials produced on a large scale, especially by the mechanically assisted LPE technique.